Produção de composto orgânico a partir de residuos de plantas medicinais - Câmara, Francisco Luiz Araújo [UNESP] (My University, 2003)
Extraction of active principles from medicinal plants generates wastes usually discharged. This process does not extract minerals from plant tissues, which may be considered of great value in organic composting. Wastes of 81 medicinal plant species processed at Centroflora/Anidro industry were analyzed for macro and micronutrients, and according to the results, three different ways to elaborate the compost were proposed: a) wastes of medicinal plants with high content of a specific mineral, aiming to fertilize soils where would be cultivated species that need high quantities of that mineral; b) wastes with mineral contents in order to support specific failures on mineral content of a soil; c) wastes of the eleven richest species in each nutrient that should elevate all mineral contents in soil.
Production of organic compost using medicinal plants wastes
Keywords: Medicinal plants; Mineral nutrition; Organic chemicals; Waste products; fertilizer; mineral; organic compound; trace element; compost; drug manufacture; macronutrient; medicinal plant; nonhuman; plant tissue; pollution; soil analysis; soil fertilization; species; waste management